Implementation and Performance Analysis of Temperature and Humidity Monitoring System for Server Room Conditions on Lora-Based Networks - Effendi, Siti Zubaidah; Oktiawati, Unan Yusmaniar (Journal of Internet and Software Engineering, 2022)
Abstract – A server room is a room used to store applications, data and network devices such as routers. The server room is the data center of a company or institution in which there are applications and databases that store all important and valuable information for the company or institution concerned, therefore the server room must always be in good temperature conditions because the devices work for 24 hours no stopping. If there is a significant increase in temperature, it can cause system performance to be disrupted or hardware damage occurs. The cooler in the server room is not optimal because the cooler is often constrained by frequent power outages. From these problems, a solution is needed to be able to monitor the system remotely so that changes in room temperature can be seen in real time. The Internet of Things (IoT) is the solution to this problem, by using LoRa, which then sends the data to the Telegram application that has been installed on the smartphone so that real-time temperature changes can be obtained